+0  
 
0
35
1
avatar

Solve for x:

(3x + 12)(3x + 4) = (4x^2 + 8x + 18x^2)/(2x).

 Jun 22, 2022
 #1
avatar+124509 
+1

(3x + 12)(3x + 4) = (4x^2 + 8x + 18x^2)/(2x)       

 

9x^2 + 48x + 48  =  ( 2x)  ( 2x + 4 + 9x)  / (2x)     .....  assuming that x  does not  = 0 

 

9x^2 + 48x + 48  =  2x + 4 + 9x

 

9x^2 +  48x + 48  = 11x  + 4             rearrange  as

 

9x^2 + 37x + 44   =  0

 

Using the Q Formula

 

              -37 ± √ [ 37^2  - 4 *9 * 44]              -37 ± √[ -215]                -37 ± √[215] i

x  =     _______________________  =     _____________ =      _____________

                           2 * 9                                        18                                 18

 

cool cool cool

 Jun 22, 2022

13 Online Users

avatar
avatar